2007
DOI: 10.1002/elps.200600310
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an antibody microarray based on agarose‐coated slides

Abstract: Construction of an antibody microarray based on agarose-coated slidesThe antibody microarray, a high-throughput multiplex immunoassay method, has become a significant tool for quantitative proteomics studies. We describe here the strategies for optimizing the condition of antibody microarray building based on agarose-coated slides. In this study, modified glass slides were robotically printed with capture antibodies against monocyte chemoattractant protein 1 (MCP-1), then dilutions of the cytokine were applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Their performance, especially affinity and avidity, strongly affects the assay sensitivity. Moreover, an additional drawback is their limited shelf life, which limits the viability of ready-to-use antibody-based sensors [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Their performance, especially affinity and avidity, strongly affects the assay sensitivity. Moreover, an additional drawback is their limited shelf life, which limits the viability of ready-to-use antibody-based sensors [2]. …”
Section: Introductionmentioning
confidence: 99%
“…The analyte can be detected by the naked eye or fluorescent immunoassays after the antigen has been captured by an antibody encapsulated in the agarose gel that is coated on the silanized surface by physical adsorption. Such analytes include the monocyte chemoattractant protein 1 (Lv et al, 2007), antihepatitis B virus surface antigen, anti-hepatitis B virus antigen , Helicobacter hepaticus bacterium (Memisevic et al, 2009), viruses in aquatic animals , white spot syndrome virus, and lymphocystis disease virus . Recently, agarose-coated slides have been produced using new techniques, including electrospinning techniques, pore-forming techniques (Memisevic et al, 2009), and robotic printing technology (Lv et al, 2007).…”
Section: Encapsulation In Gelsmentioning
confidence: 99%
“…Such analytes include the monocyte chemoattractant protein 1 (Lv et al, 2007), antihepatitis B virus surface antigen, anti-hepatitis B virus antigen , Helicobacter hepaticus bacterium (Memisevic et al, 2009), viruses in aquatic animals , white spot syndrome virus, and lymphocystis disease virus . Recently, agarose-coated slides have been produced using new techniques, including electrospinning techniques, pore-forming techniques (Memisevic et al, 2009), and robotic printing technology (Lv et al, 2007). Xu et al (2010) compared the use of agarose gel-coatings, APTES, acrylamide, poly-L-lysine, aldehyde, sulfydryl, and amino-modified glass slides for antibody immobilization and found that agarose gel-coated glass slides gave the best results, because the porous nature of the sol-gel network is suitable for antibody entrapment and antibodies immobilized in porous sol-gel are able to interact with external chemical species or analytes easily (Gupta and Chaudhury, 2007).…”
Section: Encapsulation In Gelsmentioning
confidence: 99%
“…The slides were thoroughly washed with Milli-Q water (Millipore, Billerica, MA, USA) and dried overnight at 140 • C. The slides were then modified with amine (Duburcq et al, 2004a), aldehyde (Zammatteo et al, 2000), poly-llysine (Haab et al, 2001), agarose (Afanassiev et al, 2000;Lv et al, 2007), polyacrylamide (Angenendt et al, 2002) and nitrocellulose (Kiernan, 1999), respectively. The modified glass slides were stored in desiccators at 4 • C.…”
Section: Surface Derivatization Of Glass Slidesmentioning
confidence: 99%
“…Before immobilization of protein probes, the chemically modified glass slides were activated in a 20 mM solution of NaIO 4 at room temperature for 30 min, then thoroughly washed three times in deionized water, and dried with an argon flow (Lv et al, 2007).…”
Section: Fabricating Of Protein Microarraymentioning
confidence: 99%